Very Early Passive Cycling Exercise in Mechanically Ventilated Critically Ill Patients: Physiological and Safety Aspects - A Case Series - Camargo Pires-Neto, Ruy (Public Library of Science, 2013)
INTRODUCTION: Early mobilization can be performed in critically ill patients and improves outcomes. A daily cycling exercise started from day 5 after ICU admission is feasible and can enhance functional capacity after hospital discharge. In the present study we verified the physiological changes and safety of an earlier cycling intervention (< 72 hrs of mechanical ventilation) in critical ill patients. METHODS: Nineteen hemodynamically stable and deeply sedated patients within the first 72 hrs of mechanical ventilation were enrolled in a single 20 minute passive leg cycling exercise using an electric cycle ergometer. A minute-by-minute evaluation of hemodynamic, respiratory and metabolic variables was undertaken before, during and after the exercise. Analyzed variables included the following: cardiac output, systemic vascular resistance, central venous blood oxygen saturation, respiratory rate and tidal volume, oxygen consumption, carbon dioxide production and blood lactate levels. RESULTS: We enrolled 19 patients (42% male, age 55±17 years, SOFA = 6 ± 3, SAPS3 score = 58 ± 13, PaO(2)/FIO(2) = 223±75). The median time of mechanical ventilation was 1 day (02), and 68% (n=13) of our patients required norepinephrine (maximum concentration = 0.47 µg.kg (-1).min(-1)). There were no clinically relevant changes in any of the analyzed variables during the exercise, and two minor adverse events unrelated to hemodynamic instability were observed. CONCLUSIONS: In our study, this very early passive cycling exercise in sedated, critically ill, mechanically ventilated patients was considered safe and was not associated with significant alterations in hemodynamic, respiratory or metabolic variables even in those requiring vasoactive agents.